Influence of calcination and GGBS addition in preparing β-hemihydrate synthetic gypsum from phosphogypsum - Longjian Zhang; Kim Hung Mo; Tee How Tan; Chung-Chan Hung; Soon Poh Yap; Tung-Chai Ling (Case Studies in Construction Materials, 2023)
Transforming phosphogypsum (PG) to β-hemihydrate PG with cementitious properties at low calcination temperature is an effective method for large-scale utilization of by-product PG. Nevertheless, due to the poor water resistance of PG, its application and recycling rate is limited. This study aims to produce water-resistant β-hemihydrate synthetic gypsum (SG) with minimum cost and energy consumption, using calcined PG as the raw material. The effect of PG calcination temperature (100 °C, 140 °C, 180 °C, and 220 °C) on the properties of SG was evaluated, and it was found that 180 ºC calcination temperature was able to fully convert the PG to β-hemihydrate SG. Additionally, SG prepared using 180 ºC calcined PG exhibited the highest compressive strength (9.15 MPa). On the other hand, various contents of the mineral admixture, namely, GGBS (5 %, 10 %, 15 %, 20 %, and 25 %), were incorporated in SG to evaluate the viability of GGBS to improve the compressive strength and water resistance of SG. However, the results revealed that adding GGBS has little effect on the performance of SG. Especially, when 25 % GGBS was added, the compressive strength of SG was reduced by 66.3 %. Consequently, further investigation into how to enhance the effect of GGBS is required.